Sensors and transducers - Sinclair, Ian Robertson (Newnes, 2001)
In this book Ian Sinclair provides the practical knowhow required by technician engineers, systems designers and students. The focus is firmly on understanding the technologies and their different applications, not a mathematical approach. The result is a highly readable text which provides a unique introduction to the selection and application of sensors, transducers and switches, and a grounding in the practicalities of designing with these devices. The devices covered encompass heat, light and motion, environmental sensing, sensing in industrial control, and signal-carrying and non-signal sw.